(untitled) (Iraqi Journal of Medical Sciences, 2023)
Background: The pre-sarcopenia is a preclinical state of sarcopenia; which was identified as an age associated muscle disease detected by low muscle mass only and normal muscle function. It can predict the subsequent functional decline. Objective: To estimate the prevalence of presarcopenia in Iraqi sample aged ?60 years old and determines some socio-demographic factors that may be related. Methods: A descriptive cross-sectional community dwelling study. The data obtained from a questionnaire (socio-demographic and behavioral data) in addition to anthropometry and muscle strength measurements. The muscle mass was estimated by anthropometry equation and cutoff points were derived from The European Working Group on Sarcopenia in Older People 2019. Results: The result revealed that near quarter of the sample was pre-sarcopenia; 38.3% male and 8.2% female. It was significantly associated with male, single, retirement, smokers, alcoholic, diabetic and normal body mass index elderly, it negatively related to age and fall history and positively with schooling and physically activate. Conclusion: Pre-sarcopenia, which is an age associated condition was presented as a considerable prevalence among a sample of older age participants from Baghdad and association with all independent variables. Keywords: Fragile, old age, disability Citation: Al-Taglubee IM, Al-Saffar AJ. Estimation of pre-sarcopenia among a sample aged 60 years and older from Baghdad. Iraqi JMS. 2023; 21(2): 269-277. doi: 10.22578/IJMS.21.2.15